Heat Transfer Performance in a Vertical Grooved Thermosyphon. (August 2021) - Hammouda, M.G.; Ewing, D.; Zaghlol, A.; Ching, C.Y.
Abstract: The performance of a grooved copper-water thermosyphon with a modest bend between a vertical evaporator section and inclined condenser section was characterized for a moderate fluid loading. The time-averaged temperature varied significantly along the evaporator for heat fluxes up to 10 W/cm 2 before becoming more uniform at higher heat fluxes. Transients of the measured temperatures show evidence of different flow regimes that were compared to existing flow pattern maps. The evaporator performance for both the pool region, which had the highest temperature, and the film region were not well predicted for heat fluxes up to 10 W/cm 2 . The local evaporator performance changed with the change in flow regime, suggesting the need for a flow regime-based performance model. The performance of the condenser appeared to depend on the reduced pressure and was significantly overpredicted by the standard condensation models. A modified model for the condenser was proposed.